TRANSFORMASI MANAJEMEN LEMBAGA PENDIDIKAN MENENGAH ISLAM DALAM ERA DIGITALISASI PENDIDIKAN DI SMA IBA PALEMBANG - Rauzatul Jannah; Lailatussaadah Lailatussaadah (Hijri, 2026)
This study aims to analyze the influence of public relations management courses on the communication competence of Islamic Education Management students of UIN Ar-Raniry Banda Aceh. A quantitative approach is used by collecting data through a questionnaire through a Google Form that has been validated by experts. The sample consisted of 92 students of the class of 2023 from a population of 125, determined based on the Krejcie and Morgan tables for proportional representation. The analysis was performed with Structural Equation Modeling Partial Least Squares (PLS-SEM) using SmartPLS, including convergent validity tests (outer loading >0.70, AVE >0.50), reliability (Cronbach's Alpha >0.70), and bootstrapping for path coefficients, T-statistics, and R-squares. The results of the data analysis found that the Public Relations Management and Public Relations course had a positive and significant effect on communication competence with a path coefficient of 0.817, T-statistics of 19.319 (p<0.001), and R-square of 0.668. Therefore, this course is effective in shaping students' communication competencies through applied learning.